Actinobacteria: an underestimated source of potential microbial biocontrol agents against fusarium-related diseases in cultivated crops - Djemouai, Nadjette; Meklat, Atika; Yekkour, Amine; Verheecke-Vaessen, Carol (Springer, 2023)
Crop infections with Fusarium spp. and associated mycotoxins have devastating economic implications and are a significant limitation to fifteen of the seventeen United Nations Sustainable Development Goals. Therefore, it is necessary to develop innovative strategies to reduce or eliminate diseases caused by Fusarium spp. in cultivated crops. Management of Fusarium-related diseases using beneficial microorganisms is a promising and eco-friendly solution. In this context, actinobacteria are considered one of the best candidates because of their multifunctional properties, which consist in the reduction of Fusarium spp. diseases and the promotion of plant growth. Actinobacteria represent a large Gram-positive bacterial phylum that is widespread in different environments, especially in soil. They are principally known for their versatile capacity to produce biologically active molecules with potential applications in different fields, including agriculture. As Fusarium species threaten diverse crops worldwide and cause global yield and quality losses that can negatively impact food security, the use of actinobacteria for plant diseases management is gaining interest as a safer and more potent alternative to ineffective synthetic-based pesticides. Thus, this work aims to review and highlight the importance of actinobacteria as microbial biocontrol agents and discuss the current research on Fusarium spp. diseases with a focus on species that threaten economically important crops, such as F. graminearum, F. oxysporum, F. solani, and F. culmorum. This review also presents actinobacteria-based products that have been patented for Fusarium disease control. We aim to provide valuable data, guidance and advancements for future research on microbial biocontrol against Fusarium-related diseases. In addition, this review emphasizes the need for further research about the impact of actinobacteria-Fusarium interactions on mycotoxin production. It also highlights the need of in-depth understanding microbial biocontrol mechanisms to ensure safe and sustainable crop production worldwide.
Keywords: Actinobacteria; Antibiosis; Microbial biological control; Fusarium diseases; Mycotoxins